Peran World Wide Fund dalam Menanggulangi Perdagangan Ilegal Harimau Sumatera di Riau - Ramadhanty, Sarahswati; Putranti, Ika Riswanti; Susiatiningsih, Hermini (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
The dynamics of international politics in the era of globalization are faced with variousimportant issues such as environmental conservation. One of the issues that arises is illegaltrading of Sumateran tiger in Riau Province. In this study the authors will describe moreabout the involvement of International Organizations namely World Wide Fund (WWF) tohandle the endangered species trade issues. This study used several approaches such as theNeoliberal institutional theory, the Transnational crime theory, the theory of Internationalcooperation, and the International organization theory. While the method used in this studyis descriptive qualitative with secondary method data collecting. This study concluded thatthe role of WWF to handle the Sumateran tiger illegal trading issues is realized throughinformational / promotional activity, collaboration, and cooperation with Goverment,implementation of collaboration program at home and abroad, formation ofcommunication channel and monitoring. These efforts have made progress in supportingthe conservation of endangered species, although they cannot be the fundamental solution.